(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Today, the teaching of English has changed from traditional classroom methods to more open and diverse practices. The competency in English language is currently assessed as an employability skill for collaboration and authentic communication such as job interviews and international projects. This increased the demand for skilled language teachers who are proficient in technical and professional English. It is true that Massive Open Online Courses has made learning more flexible. Internet is connecting and widening the scope for teachers and learners. Students can now become more self-directed and active in their own learning processes. To be competent and to survive in this ever changing field of English language teaching, the English teachers have to reach the open and flexible platform of e-learning, and remain up-to-date. Use of Web 2.0 services, video lectures, podcasting, tablet computers and mobile apps can assist the teachers of English to make leaning more open, effective and massive, fast and user oriented.